Propranolol in the treatment of infantile haemangiomas: Lessons from the European Propranolol In the Treatment of Complicated Haemangiomas (PITCH) Taskforce Survey. - IRVINE, ALAN (My University, 2015)
BACKGROUND: Oral propranolol is widely prescribed as first line treatment for infantile haemangiomas (IHs) and anecdotally prescribing practice differs widely between centres. OBJECTIVES: The Propranolol In the Treatment of Complicated Haemangiomas (PITCH) Taskforce was founded to establish patterns of use of propranolol in IHs. METHODS: Participating centres entered data on all of their patients who had completed treatment with oral propranolol for IHs, using an online data capture tool. RESULTS: The study cohort comprised 1096 children from 39 centres in eight European countries. 76.1% were female and 92.8% had a focal IH, with the remainder showing a segmental, multifocal or indeterminate pattern. The main indications for treatment were periocular location (29.3%), risk of cosmetic disfigurement (21.1%), and ulceration and bleeding (20.6%). 69.2% of patients were titrated up to a maintenance regimen, which consisted of 2mg/kg/day (85.8%) in the majority of cases. 91.4% of patients had an excellent or good response to treatment. Rebound growth occurred in 14.1% upon stopping, of which 53.9% were restarted and treatment response was recaptured in 91.6% of cases. While there was no significant difference in the treatment reponse, comparing a maintenance dose of <2mg/kg/day versus 2mg/kg/day versus >2mg/kg/day, the risk of adverse events was significantly higher (OR=1 vs adjusted OR=0.70 (0.33-1.50), p=0.36 vs 2.38 (1.04-5.46), p=0.04, ptrend <0.001). CONCLUSIONS: The PITCH survey summarises the use of oral propranolol across 39 European centres, in a variety of IH phases and could be used to inform treatment guidelines and the design of an intervention study. This article is protected by copyright. All rights reserved.
PUBLISHED
Keywords: Oral propranolol